Mapeando os valores subjetivos dos gerentes de relacionamento em negociações bancárias - Pegorer Junior, Alcides (2012)
In the context of a very competitive market, having teams very well prepared and properly allocated is critical to the survival of businesses. This study aims to identify the repercussion on customer satisfaction and results of companies, from the knowledge of the people working on the front line of these companies, those professionals who play an important role in negotiation, identifying what they value in a subjectively negotiation. Using the tool SVI (Subjective Value Inventory) developed by Curhan et al (2006), from the dimensions of independent and interdependent self-image, attempts to identify the subjective values of the negotiators of a Brazilian retail bank, responsible for a significant part of the negotiations and results of the company in relation to feelings about themselves (Self), the instrumental results, and the process and relationship (Rapport), using interpersonal trust as a moderator in this relationship. Once identified, found results will be related to the customer satisfaction. The purpose of seeking this correlation is due to the assumption that the company exists only because of the customer. For this purpose, it was conducted a quantitative survey, with the application of a structured and closed questionnaire to 532 of the bank negotiators from that bank, who work in the states of Santa Catarina, Rio de Janeiro and Maranhão, responsible for relationship, prospecting and conducting business with institution’s customers, personal, small business and government. Data were analyzed using statistical techniques, using the method of Partial Least Squares. It was observed that over forty percent of customer satisfaction is explained by the subjective values of the negotiators. The study showed, among others results, that business managers with self-image independently value the Self and instrumental results in a negotiation, and interpersonal trust cognitive negatively moderates this relationship. Still, Rapport is valued in a negotiation by those business managers with interdependent self-image and this appreciation in a negotiation is positively related to customer satisfaction.